IMPLEMENTING THE CAKE APPLICATION IN STUDENTS' ENGLISH CLASSROOM - Steviana Kristanti; Herlina Herlina; Ferri Hidayad (Esteem Journal of English Education Study Programme, 2024)
The impact of technology on contemporary living is substantial. Program changes are required in education to close the gap between present and future teaching and learning technology. During the learning process, using applications as instructional material is a workable strategy. Finding out how to use the Cake Application in English classes for students and examining the opportunities and difficulties encountered in doing so at Vocational High School 8, Palembang, are the goals of this research. Data were gathered by the researcher using observation, questionnaires, and documentation, all of which were qualitative methods. The outcome demonstrates that the Cake application is successfully used in the English language learning process and can boost students' motivation to learn the language. The Cake app is user-friendly, free of intrusive advertisements, packed with features, and offers a ton of videos arranged according to quiz level and category. Additionally, students can improve their grades and fix errors with the Cake program. One of the difficulties in utilizing this software for both students and teachers is that not every curricular item can be found in the Cake app, therefore educators have to make adjustments. The Internet connection, smartphone batteries, smartphone storage capacity, and the requirement for hearing aids for the listening phase were more issues.